Extemal counter-pulsation effects on left ventricular myocardial perfusion in patients with coronary heart disease - I. V. Sergienko; S. A. Gabrusenko; V. V. Malakhov; M. E. Bugriy; V. B. Sergienko (Кардиоваскулярная терапия и профилактика)
Aim. To assess the effects of enhanced external counter-pulsation (EECP) on left ventricular (LV) myocardial perfusion.Material and methods. In total, 26 patients with coronary heart disease (CHD), stable angina, Functional Class (FC) I-IV, were treated with EECP. Treatment course included 35 one-hour procedures. At baseline and after EECP treatment, all patients underwent 99m-Tc-MIBI scintigraphy (single photon emission computed tomography, SPECT) at rest and during stress test.Results. After EECP treatment, perfusion defect severity assessed by SPECT at rest had significantly reduced (p<0,01). Pre- and post-EECP perfusion defect areas were 18,0±13,6 % and 17,2±15,7 %, respectively (p>0,05); pre- and post-EECP perfusion defect severity - 347,3±282,8 and 310±266,0 std, respectively (p<0,01). No significant dynamics of perfusion defect area or severity was observed for stress EECP.Conclusion. EECP treatment was associated with improved LV myocardial perfusion in CHD patients.